Dibutyryl Cyclic Adenosine Monophosphate Rescues the Neurons From Degeneration in Stab Wound and Excitotoxic Injury Models - Abd-El-Basset, Ebtesam M.; Rao, Muddanna S. (Frontiers in Neuroscience, 2018)
Dibutyryl cyclic adenosine monophosphate (dBcAMP), a cell-permeable synthetic analog of cAMP, has been shown to induce astrogliosis in culture. However, the exact mechanism underlying how dBcAMP exerts its function in situ is not clear. The objective of this study was to examine the effects of dBcAMP on astrogliosis and survival of neurons in stab wound and kainic acid models of brain injury. Stab wound was done in cerebral cortex of BALB/c male mice. Kainic acid lesion was created in hippocampus by injecting 1µl kainic acid into the lateral ventricle. Animals in both models of injury were divided into L+dBcAMP and L+PBS groups and treated with dBcAMP or PBS for 3, 5 and 7 days respectively. The brain sections were stained for Cresyl violet and Fluro jade-B to assess the degenerating neurons. Immunostaining for GFAP and Iba-1 was done for assessing the astrogliosis and microglial response respectively. Expression of GFAP and BDNF levels in the tissue were estimated by Western blotting and ELISA respectively. The results showed a gradual increase in the number of both astrocytes and microglia in both injuries with a significant increase in dBcAMP-treated groups. The number of degenerating neurons significantly decreased in dBcAMP treated groups. In addition, it was found that dBcAMP stimulated the expression of GFAP and BDNF in both stab wound and kainic acid injuries. Treatment with BDNF receptor inhibitor AZ-23, showed an increase in the degenerating neurons suggesting the role of BDNF in neuroprotection. This study indicates that dBcAMP protects neurons from degeneration by enhancing the production of BDNF and may be considered for use as therapeutic agent for treatment of brain injuries.